2000
DOI: 10.1289/ehp.001081189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dibutyl phthalate as an environmental endocrine disruptor on gonadal sex differentiation of genetic males of the frog Rana rugosa.

Abstract: To examine the effects of dibutyl phthalate (DBP) on gonadal sex differentiation, genetically male tadpoles of Rana rugosa were exposed to dilute solutions of DBP at concentrations of 0.1, 1, or 10 microM during days 19-23 after fertilization, which is the critical period of gonadal sex differentiation in R. rugosa. Tadpoles were necropsied on day 40. The genetically male tadpoles were produced from crossings between males (ZZ) of one local population, in which females are the heterogametic sex, and females (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 35 publications
3
33
1
Order By: Relevance
“…Another ester, di-n-butyl phthalate (DBP), induced the occurrence of intersex specimens and sex inversion in studies conducted on genetic males of the Japanese wrinkled frog (Rana rugosa) (Ohtani et al, 2000). Also, following exposure to DBP, the African clawed frog (Xenopus laevis), exhibited delayed spermatogenesis and symptoms of feminisation manifesting as well-developed fallopian tubes in the testes (Lee and Veeramachaneni, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Another ester, di-n-butyl phthalate (DBP), induced the occurrence of intersex specimens and sex inversion in studies conducted on genetic males of the Japanese wrinkled frog (Rana rugosa) (Ohtani et al, 2000). Also, following exposure to DBP, the African clawed frog (Xenopus laevis), exhibited delayed spermatogenesis and symptoms of feminisation manifesting as well-developed fallopian tubes in the testes (Lee and Veeramachaneni, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental Health Perspectives • VOLUME 111 | NUMBER 4 | April 2003 intersexuality induced by PCB 3 and PCB 5 in X. laevis as well as previous studies suggest that endocrine disruptors can affect gonadal differentiation in amphibians and that this kind of chemical may be a factor leading to population declines (Hayes et al 2002;Kloas et al 1999;Ohtani et al 2000Ohtani et al , 2001. Therefore, it is necessary to develop a model using a representative species to study the effects of endocrine disruptors on amphibians.…”
Section: Articles | Effects Of Chinese Pcbs On Xenopus Laevismentioning
confidence: 99%
“…Certainly, other amphibian species might have also their own advantages. For example, genetic males in Rana rugosa can be induced (Ohtani et al 2000), and feminization in Hyperolius argus can be identified directly by sex coloration (Noriega and Hayes 2000). However, the most serious disadvantage of these species is that they have not been used broadly as typical experimental animals.…”
Section: Articles | Effects Of Chinese Pcbs On Xenopus Laevismentioning
confidence: 99%
See 1 more Smart Citation
“…Amphibians are susceptible to environmental contaminants because of their permeable skins and a biphasic life cycle [11,12]. Increasing evidence suggests that gonadal development of amphibians is especially sensitive to endocrine disruptors [13][14][15]. Although high accumulation of PCBs in wild amphibians highlights the need to examine the potential role of PCBs in the amphibian population, the available information regarding toxic effects of PCBs on amphibians has been very limited so far [16,17].…”
Section: Introductionmentioning
confidence: 99%